EFEK DIET MEDITERANIA TERHADAP KONTROL GLIKEMIK DAN SENSITIVITAS INSULIN PADA PASIEN DIABETES MELITUS: SEBUAH TINJAUAN SISTEMATIS DAN META-ANALISIS - Astuti, Komang Puji; Sasmana, I Gede Aswin Parisya; Subrata, I Made (Essence of Scientific Medical Journal; Vol 21 No 2 (2024): Volume 21 No. 2 (Juli - Desember 2023) Essential: Essence of Scientific Medical Journal, 2024)
Introduction: Type 2 diabetes mellitus (T2DM) has become a global concern with a prevalence reaching 6.28% worldwide which is characterized by insulin resistance, chronic increases in blood glucose, and contributes to the development of various diseases with high mortality. Several dietary approaches have been developed to improve T2DM, including the Mediterranean diet, which has not been widely evaluated. Methods: This literature was created to evaluate the effect of the Mediterranean diet on glycemic control and insulin sensitivity in T2DM patients. Methods: A systematic review and meta-analysis was used to create this literature, including valid clinical studies and retrieved from PubMed, ScienceDirect, and Cochrane databases until July 2023. A total of 7 studies involving 1395 participants were included and analyzed using Review Manager and R to evaluate control glycemia, insulin resistance, and Body Mass Index (BMI). Results: The results of the study showed that the Mediterranean diet was able to reduce blood glucose levels significantly (MD -0.69; 95%CI: -1.08 to -0.29; I2 = 67%; p: 0.0006), both fasting and non-fasting blood glucose. Apart from that, this diet can also reduce HbA1c significantly compared to the control diet (MD -0.45; 95%CI: -0.68 to -0.21; I2 = 63%; p: 0.0003). In reducing insulin resistance, the Mediterranean diet can significantly reduce HOMA-IR with a difference in protective ratio of -0.82 (95%CI: -1.29 to -0.36; I2 = 79%; p=0.0005). Moreover, the Mediterranean diet can reduce BMI in T2DM patients (MD: -0.66; 95%CI: -0.98 to -0.34; I2 = 44%; p<0.00001) which can certainly prevent further severity and complications of this disease. Conclusion: The Mediterranean diet can reduce fasting, non-fasting blood glucose levels, HbA1c, HOMA-IR, and BMI in T2DM